Vaccination With Viral Vectors Expressing Chimeric Hemagglutinin, NP and M1 Antigens Protects Ferrets Against Influenza Virus Challenge - McMahon, Meagan; Asthagiri Arunkumar, Guha; Liu, Wen-Chun; Stadlbauer, Daniel; Albrecht, Randy A.; Pavot, Vincent; Aramouni, Mario; Lambe, Teresa; Gilbert, Sarah C.; Krammer, Florian (Frontiers in immunology, 2019)
Seasonal influenza viruses cause significant morbidity and mortality in the global population every year. Although seasonal vaccination limits disease, mismatches between the circulating strain and the vaccine strain can severely impair vaccine effectiveness. Because of this, there is an urgent need for a universal vaccine that induces broad protection against drifted seasonal and emerging pandemic influenza viruses. Targeting the conserved stalk region of the influenza virus hemagglutinin (HA), the major glycoprotein on the surface of the virus, results in the production of broadly protective antibody responses. Furthermore, replication deficient viral vectors based on Chimpanzee Adenovirus Oxford 1 (ChAdOx1) and modified vaccinia Ankara (MVA) virus expressing the influenza virus internal antigens, the nucleoprotein (NP) and matrix 1 (M1) protein, can induce strong heterosubtypic influenza virus-specific T cell responses in vaccinated individuals. Here, we combine these two platforms to evaluate the efficacy of a viral vectored vaccination regimen in protecting ferrets from H3N2 influenza virus infection. We observed that viral vectored vaccines expressing both stalk-targeting, chimeric HA constructs, and the NP+M1 fusion protein, in a prime-boost regimen resulted in the production of antibodies toward group 2 HAs, the HA stalk, NP and M1, as well as in induction of influenza virus-specific-IFNγ responses. The immune response induced by this vaccination regime ultimately reduced viral titers in the respiratory tract of influenza virus infected ferrets. Overall, these results improve our understanding of vaccination platforms capable of harnessing both cellular and humoral immunity with the goal of developing a universal influenza virus vaccine.